2003
DOI: 10.1046/j.1461-0248.2003.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of functional diversity across an extensive environmental gradient: vertebrate consumers, hidden treatments and latitudinal trends

Abstract: Over the last two decades, although much has been learned regarding the multifaceted nature of biodiversity, relatively little is known regarding spatial variation in constituents other than species richness. This is particularly true along extensive environmental gradients such as latitude. Herein, we describe latitudinal gradients in the functional diversity of New World bat communities. Bat species from each of 32 communities were assigned to one of seven functional groups. Latitudinal gradients existed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
190
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(202 citation statements)
references
References 39 publications
4
190
2
6
Order By: Relevance
“…Previous studies on bat and avian assemblages have shown lower FD within local assemblages than expected by chance [41,43]. This study does not uniformly support these results on a continental scale for large carnivores.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies on bat and avian assemblages have shown lower FD within local assemblages than expected by chance [41,43]. This study does not uniformly support these results on a continental scale for large carnivores.…”
Section: Discussioncontrasting
confidence: 91%
“…For example, fish assemblages in Europe and North America have consistent trait-based responses to hydrologic variability, supporting a significant degree of convergent evolution of the species pools and consistent niche assembly [79]. Trait diversity in bat assemblages decreases with latitude and is highly dependent on regional diversity [80]. In Mediterranean shrublands, mean plant traits change with successional age [41].…”
Section: Recent Advances (A) Changes In Vocabularymentioning
confidence: 93%
“…One expects strong interactions to select for ecological specialization, but it is difficult to assess this without knowing patterns of resource utilization. In the case of terrestrial birds and bats, both of which exhibit strong latitudinal gradients in diversity, tropical environments support many species that use resources, such as nectar, fruit, and large insects, not perennially available in temperate latitudes (30)(31)(32). However, even among ecologically homogeneous phylogenetic groups, including many families of passerine birds, tropical regions harbor many more species than temperate regions.…”
mentioning
confidence: 99%